1987
DOI: 10.2307/2056667
|View full text |Cite
|
Sign up to set email alerts
|

Caste, State, and Ethnic Boundaries in Nepal

Abstract: Models of ethnicity in Nepal stress, on the one hand, unlimited ethnic diversity and, on the other, a rather limited set of ethnic contrasts: Hindu versus Buddhist, tribe versus caste, mountain versus middle hills versus lowland Terai. However, ethnic relations in Humla District, in Nepal's far northwest Karnali Zone, are characterized more by interaction, interdependence, and mobility than contrasts and boundaries between groups.1 In Humla, individuals and even entire villages readily change their ethnic affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…In our FGDs, participants also explained that increasing involvement in social and financial organization and access to credit from women groups, micro-finance, and banks have attributed starting small enterprises such as grocery stores, restaurants, goat-keeping, poultry farming, and other income-generating activities such as tailoring. Caste and ethnic affiliation traditionally used to play a strong role in economic status and LS choice in Nepal [73]. The results showed that households in the Brahmin and Tharu communities are less likely to adopt lucrative LS than those in the Janajati, Chhetri, and Dalit communities.…”
Section: Determinants Of Livelihood Strategymentioning
confidence: 91%
“…In our FGDs, participants also explained that increasing involvement in social and financial organization and access to credit from women groups, micro-finance, and banks have attributed starting small enterprises such as grocery stores, restaurants, goat-keeping, poultry farming, and other income-generating activities such as tailoring. Caste and ethnic affiliation traditionally used to play a strong role in economic status and LS choice in Nepal [73]. The results showed that households in the Brahmin and Tharu communities are less likely to adopt lucrative LS than those in the Janajati, Chhetri, and Dalit communities.…”
Section: Determinants Of Livelihood Strategymentioning
confidence: 91%
“…Gorenburg (2000) revealed that support for nationalism within an ethnic group is neither constant nor random. To what extent caste classification depends on context has been reported by Levine (1987) and Berreman (1972). Brubaker et al (2006) show in their study of an ethnically mixed town in Transylvania that despite elite-level nationalist discourses against the ethnic minority, ordinary people of both the majority and minority do not seem to be preoccupied very much by questions of ethnic differences.…”
Section: The Actors' Perceptions and Categorisationsmentioning
confidence: 99%
“…Further, the caste/ethnic identity of others is readily identifiable for most Nepalis, either from surnames or contextual information. The particular salience of caste and ethnic identity in Nepal can be traced back to the Rana regime and the Muluki Ain, which formalized the orthodox Hindu ideology and classifications of Prithvi Narayan Shah (Hofer, 1979;Levine, 1987). This effectively fused the religious notion of the dharmasutras to the civil and criminal laws of Nepal (Hofer, 1979;Gellner, 2007), creating legal separation between the elite wearers of sacred thread (Tagadhari) and the alcohol-consuming classes (Matwali).…”
Section: Caste Ethnicity and Identity In Nepalmentioning
confidence: 99%